Campaigning for Judicial Office, 2012 - Zuercher, Robert J (2015)
Concerns over the way in which judicial campaigns are conducted have been voiced since the 1970s. Judicial elections are thought to have become rough and tumble contests, featuring increasing campaign expenditures and controversial campaign speech. With the widespread deregulation of judicial candidate campaign speech in the early 2000s, scholars have become increasingly concerned with how judicial candidates campaign. This dissertation examines the role of the media in judicial elections, campaign communication methods used by candidates, how candidates develop campaign messages, controversial campaign speech, the consequences of campaigning, and candidates’ attitudes toward judicial selection reform. Data gathered from a survey of judicial candidates who ran for election in 2012 (n = 490) and follow-up interviews with candidates (n = 35) were used to address the research questions posed by this investigation. Findings reveal a number of areas of concern with judicial elections beyond campaign speech, including lack of media coverage, lack of access to adequate communication channels, and concerns over external group involvement in judicial elections. Controversial speech is rare in judicial campaigns and few candidates favor strong speech regulations, which are viewed as barriers between the office and the public